The Role of Mesenchymal Stem Cells in the Induction of Cancer-Stem Cell Phenotype - Jing, Yuanming; Liang, Wenqing; Zhang, Lin; Tang, Junjun; Huang, Zongliang (Frontiers in Oncology, 2022)
Cancer stem cells (CSCs) modify and form their microenvironment by recruiting and activating specific cell types such as mesenchymal stem cells (MSCs). Tumor-infiltrating MSCs help to establish a suitable tumor microenvironment for the restoration of CSCs and tumor progression. In addition, crosstalk between cancer cells and MSCs in the microenvironment induces a CSC phenotype in cancer cells. Many mechanisms are involved in crosstalk between CSCs/cancer cells and MSCs including cell-cell interaction, secretion of exosomes, and paracrine secretion of several molecules including inflammatory mediators, cytokines, and growth factors. Since this crosstalk may contribute to drug resistance, metastasis, and tumor growth, it is suggested that blockade of the crosstalk between MSCs and CSCs/cancer cells can provide a new avenue to improving the cancer therapeutic tools. In this review, we will discuss the role of MSCs in the induction of cancer stem cell phenotype and the restoration of CSCs. We also discuss targeting the crosstalk between MSCs and CSCs/cancer cells as a therapeutic strategy.